Species richness and indices of abundance of medium-sized mammals in andean forest and reforestations with andean alder: a preliminary analysis (2008)
We studied the species richness and two indices of abundance of medium-sizedmammals in areas with Andean forest and Andean alder (Alnus acuminata)reforestations in a reserve at the Central Andes of Colombia. Since reforested areashave a less complex habitat structure and lower plant diversity than native forests, wepredicted that they have lower richness of mammals than areas with Andean forest.We obtained the indices of abundance from direct contacts in transects and from theuse of track stations. Our results suggest that, indeed, areas with Andean forest hada higher richness of mammals than reforestations, but this pattern may be modifiedby anthropogenic factors. We found no differences between the indices of abundanceof the squirrel, Sciurus granatensis, in the two forest types. In contrast, the coatiswere recorded more frequently in the reforestations than in areas with Andean forestat the reserve.